Coping Strategies to face the stress quarantine of the virus Covid-19 among a sample of higher education professors who returned from abroad "An Exploratory Study - Meliani, abdelkarim; madjadi, mestapha (Social Empowerment Journal, 2020)
The study aimed at identifying coping strategies to face the psychological stress confinement of the Covid virus-19 among professors of higher education who returned from abroad. The descriptive analytical method was used on an intentional sample consisting of 60 male and female professors who were exposed to quarantine in various hotels in Algeria as a result of the spread of the Covid virus-19 . After data collection, using an electronic questionnaire , they were introduced to statistical package system for the social sciences spss v22.The results of the study showed that the degree of hotel commitment of higher education professors who returned from abroad is high, and the coping strategies to face psychological pressure among them during the quarantine period are astrategy of adherence to the quarantine law, then an ethical religiousstrategy and finally a preventive health strategy,